Replacement of fish oil with engkabang butter oil (Shorea macrophylla): Effects on growth performance of Javan Mahseer (Tor tambra) - Aidil Ikhwan Redhwan; Nurul Aina Nadhirah Mohd Khairulnizam; Nurul Ashikin Mohamad Zuki; Nur Hamna Aminudin; Connie Fay Komilus (Penerbit Universiti Kebangsaan Malaysia, 2023)
The effectiveness of Shorea macrophylla butter oil (SMBO) as a replacement for fish oil on the growth performance of Javan Mahseer (Tor tambra) is still understudied. The purpose of this research was to examine the proximate composition, fatty acid profile, and efficacy of SMBO as an alternative lipid source to replace fish oil on the growth performance of Tor tambra (Javan mahseer). A 1-month feeding trial was done using 150 tails of Javan Mahseer fingerlings with an average weight of 3.06±0.17 g, using 5 feed treatments randomly assigned in triplicates. Dietary treatments included (0%) fish oil based as control (C) and SMBO inclusion of 1.25% (T1), 2.5% (T2), 3.75% (T3) and 5% (T4) respectively. The fatty acid composition of Shorea macrophylla oil and the proximate composition of treatment diets were determined while growth indices (BWG, FCR & FI) were measured every 10 days. Water quality measurements like pH, dissolved oxygen, and temperature were taken every week. Data were analyzed using One-Way ANOVA. Results showed that BWG was higher at 45.51% after day-10 in C (5% fish oil & 0% Shorea macrophylla butter oil) while FCR were C (0.86), T1 (1.17), T2 (1.14), T3 (1.18), and T4 (1.09). It can be concluded that 5% Shorea macrophylla oil in the diet may improve the growth performance of Tor tambra fingerlings.